Low-frequency plasmonic state and tunable negative permittivity in percolative graphite / barium titanate composites. Issue 1 (1st January 2022) - Song, X.T.; Shi, Guangyue; Fan, Guohua; Liu, Yao; Fan, Runhua
Abstract: Percolative composites with negative permittivity have attracted widespread attentions due to their great potential in electromagnetic shielding and microwave devices. Targeting at achieving epsilon-negative properties, the percolative graphite/barium titanate (GR/BaTiO3 ) composite is herein designed and prepared using hot-pressing sintered process. It's found that the plasma oscillations of delocalized electrons result in the epsilon negative permittivity behaviors when the GR contents exceeds the 2 wt% (percolation threshold), and frequency dependence of the negative permittivity which is in well agreement with the Drude model. Meanwhile, it's demonstrated that the ac conductivity represents a typical metal-like behavior as the conductive networks formed within the composites by the increasing GR loadings. Moreover, the equivalent circuit analysis reveals the relationships between capacitive-inductive transition and the conversion of permittivity changing from positive to negative. This work provides effective possibility for developing excellent dielectric properties of percolative GR/BaTiO3 composite for capacitors and coil-less electrical inductors applications.